A comparative study of conceptual metaphors in Indonesian and Chinese economic headlines - Yuniarto, Hendy (citeus, 2025)
This study examines how economic concepts are metaphorically constructed in Indonesian and Chinese news headlines. Employing the Lakoff and Johnson's framework of Conceptual Metaphor Theory, the study analyzes and compares conceptual metaphors in economic news headlines from CNBC Indonesia and China Business Network published between January and April 2025. Employing a qualitative methodology guided by MIPVU, the study mapped conceptual economic metaphors in a corpus of 500 economic news headlines. The investigation demonstrates a significant overlap in the conceptualization of economic events in both languages: economic actions are physical movements, business is a natural force, economy is a competition, money is liquid, profit is up and loss is down. Despite these similarities, this research identifies unique conceptual metaphors. In the Indonesian context, unique metaphors include trade is hunting, business is a monarchy, business is a tidal cycle, business is a supernatural phenomenon, and economic actions are a martial arts skill. conversely, unique Chinese economic metaphors include business is a game, business is a historical event, business is a philosophical action, company is a martial arts school, and business is a cultural activity. This comparative study demonstrates that while universal cognitive mechanisms underpin some shared economic metaphors, the specific metaphors used in Indonesian and Chinese news headlines are strongly shaped by their unique cultures, histories, and philosophies.